Towards Usability Heuristics for Interactive Web Maps - Marquez, Juliana Orro; Meirelles, Paulo; da Silva, Tiago Silva (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
Interactive web maps are tools used to disseminate geographic information. These, unlike printed maps, allow for more significant interaction and manipulation of spatial data. However, the transformation from the physical to the digital environment often presents problems regarding the non-use of cartographic standards and user communication difficulty with an interactive map interface. In order to cover this gap, this study proposes new interface usability heuristics for interactive web maps. Following a consolidated methodology, we performed the recommended steps, from the exploratory stage to the definition of heuristics in the specification stage. Thus, we present a new set of heuristics to support the development and evaluation of maps’ usage in this context.